2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35509
|View full text |Cite
|
Sign up to set email alerts
|

Whither Engineering and Technological Literacy? Cui Bono 2

Abstract: At the 2018 Business meeting of the Technological and Engineering Literacy/Philosophy Division (TELPhE) of the American Society for Engineering Education it was agreed that the author would continue to prepare a whitepaper on the future of the Division. As part of his study for the whitepaper the author responded [1] to nine comments in the Division's fourth handbook [2] on a previously published paper by him on "Why technological literacy and for whom? [3] The principal axiom drawn from this analysis was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recent studies of the Grenfell Fire [1] and Boeing 737Max [2] tragedies to determine the nature of technological literacy as a general educational initiative have showed that something more than a requirement for technical understanding (engineering literacy) is involved; in particular, an understanding of people behaviour in organisations. As such they affirm models of engineering/technology that embrace the philosophical and social (economic) factors underpinning design and manufacture as well as the organisational structure that brings about manufacture and production.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the Grenfell Fire [1] and Boeing 737Max [2] tragedies to determine the nature of technological literacy as a general educational initiative have showed that something more than a requirement for technical understanding (engineering literacy) is involved; in particular, an understanding of people behaviour in organisations. As such they affirm models of engineering/technology that embrace the philosophical and social (economic) factors underpinning design and manufacture as well as the organisational structure that brings about manufacture and production.…”
Section: Introductionmentioning
confidence: 99%